Faktor-Faktor yang Mempengaruhi Persepsi Etis Auditor Dengan Filosofi Tri Kaya Parisudha Sebagai Variabel Pemoderasi - Utariyani, Komang Tri; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 32 No 5 (2022), 2022)
The purpose of the study was to obtain empirical evidence regarding the effect of love of money, machiavellian nature, and ethical sensitivity on auditors' ethical perceptions with the Tri Kaya Parisudha philosophy as a moderating variable. This research was conducted at 12 Public Accounting Firms. The method of determining the sample in this study used a purposive sampling technique so that a sample of 78 auditors was obtained. Data was collected using the questionnaire method. The data analysis technique used in this research is using PLS 3.0 software. Based on the results of the study, it is known that love of money has a negative effect on the ethical perception of the auditor, while the machaivellian nature and ethical sensitivity have no effect on the ethical perception of the auditor. Based on the results of the research that has been done, it is also known that the Tri Kaya Parisudha philosophy is not able to weaken the influence of love of money on the ethical perception of the auditors, while the Tri Kaya Parisudha philosophy is able to weaken the influence of Machiavellian nature and ethical sensitivity on the auditor's ethical perception. Keywords: Love of Money; Machiavellian; Ethical Sensitivity; Ethical Perception; Philosophy Tri Kaya Parisudha.